Formação e prática de um professor de matemática no contexto da educação de surdos: um estudo de caso - Silva, Iranir Pontes (2020)
The present study had as object of research the process of formation and pedagogical practice of teachers, especially of Mathematics, for an inclusive education, considering as background the difficulties of the process of literacy of deaf students. With this in mind and the challenges that teachers face in the context of inclusive education and the lack of adequate academic training to meet the current diversity that is present in schools we aim to analyze the educational trajectory and pedagogical practice of a teacher licensed in mathematics at a public school in the municipality of Nova Floresta – PB. More specifically, our objective demanded: lift the route the formation of the research subject, considering the demands of the education of deaf students; discuss the necessary knowledge to be developed to include the deaf student in Mathematics classes in Regular Education and, finally, identify and discuss the difficulties of the inclusion process in Mathematics teaching. For the development of this work, we adopted a qualitative perspective, based on the case study methodology, which involved the investigation of the formation and practice of a Mathematics teacher, postgraduate student in Neuroscience and Pedagogical Practices, who has at working in the network public school for two years and which is currently developing a work of literacy in Language and Mathematics, out of class, of deaf students in partnership with the Libras interpreter. We used as instruments of data collection: semi-structured interview conducted with the teacher and the interpreter, free observation of the practice of both and analysis of school documents producedused by the teacher, the main subject of this investigation. Data analysis was performed based on elements of the theory of Categorical Content Analysis, from the perspective of Bardin (2011), considering the categories: “Constitution of teacher training”; “Knowledge of deaf culture”; “Knowledge of educational inclusion”; "Knowledge of the performance of the Libras Interpreter" and "Knowledge of the valorization of visual experiences in teaching mathematics to deaf students". As a result of the study, we consider that, although teacher training courses are not enough, with regard to inclusive education, the actions and attitudes of the teacher and the interpreter, as a reflective professional who mobilizes knowledge to meet and contribute to the learning of their students. students, indicates the possibility of the real implementation of this educational policy.